Matters of fiber size and myonuclear domain: Does size matter more than age?. Issue 6 (28th September 2015) - Karlsen, Anders; Couppé, Christian; Andersen, Jesper L.; Mikkelsen, Ulla R.; Nielsen, Rie H.; Magnusson, S. Peter; Kjaer, Michael; Mackey, Abigail L.
ABSTRACT: Introduction : The relationship between fiber size and myonuclear content is poorly understood. Methods : Biopsy cross‐sections from young and old trained and untrained healthy individuals were analyzed for fiber area and myonuclei, and 2 fiber‐size‐dependent cluster analyses were performed. Results : When comparing fibers of similar size, no effect of training or age was found for myonuclear domain. There was a linear relationship between fiber area and myonuclei per fiber ( r  = 0.99; P  < 0.001) and a non‐linear relationship between fiber area and domain ( r  = 0.97–0.99; P  < 0.0001), with a markedly smaller domain in fibers <3, 000 µm 2 . A higher proportion of type II fibers <3, 000 µm 2 was observed in the old subjects. Conclusions : These findings suggest that age‐related reductions in myonuclear domain size could be explained by the greater proportion of small fibers. The data also highlight the usefulness of determining fiber‐size‐based clusters for gaining mechanistic insight into the relationship between skeletal muscle fiber size and myonuclear content. Muscle Nerve 52 : 1040–1046, 2015